Production cross-sections of residual radionuclides from proton-induced reactions on Ag-nat up to 40 MeV - Khandaker, Mayeen Uddin; Kim, Kwangsoo; Kim, Kyung-Sook; Lee, Manwoo; Kim, Guinyun; Cho, Young Sik; Lee, Young Ouk (Elsevier, 2008)
We measured the cross-sections of the Ag-104g,Ag-105,Ag-106m and Cd-104,Cd-107 radionuclides produced by proton-induced reactions on natural silver by using a stacked-foil activation technique in the energy range from a threshold energy to 40 MeV at a MC50 cyclotron. The results showed generally good agreement with available data as well as the theoretical data. The integral yields for thick targets were also deduced using the measured cross-sections and the stopping power of Ag-nat over the energy range from a threshold energy to 40 MeV, taking into account that the total energy is absorbed in the targets. The production cross-sections for the Ag-104g and the Cd-104 radionuclides from natural silver were measured for the first time. (C) 2008 Elsevier B.V. All rights reserved.